Technical efficiency of dairy farms in 2008-2017 - Świtłyk, Michał (Efektywność techniczna gospodarstw mlecznych w latach 2008-2017, 2020)
The aim of the study was to determine the technical efficiency of farms specialising in milk production (type 45) using the DEA method. The research covered the period 2008- 2017. Data for calculations were collected using the indirect observation method based the data from the Polish FADN Cfor2008-2017 as the source of actual data. 11055 dairy farms were included in the study. Dairy farms with fewer than 15 cows were excluded from the study. The DEA method uses an approach that minimizes inputs and the CCR and BCC models. In the description of the results, the surveyed farms were divided into three groups: effective farms for which the technical efficiency coefficient was 100%, farms close to effective, in which the technical efficiency coefficient was within <90<100% and ineffective farms, in which the analysed coefficient was smaller than 90%. In the analysis of the results of the given dairy farms, the farms were divided according to their economic size, cow herd size and milk yield
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 81-96
Keywords: DEA method; technical efficiency; production of milk; metoda DEA; efektywność techniczna; produkcja mleka